The pattern of Ippon appearance in major judo competitions in the period 2008-2009 - Rosu, D. (Journal of Physical Education and Sport, 2010)
Determining the trends manifested in the current competition judo, in relation to the incidence of the Ippon.Methods: 26 major judo competitions during 2008-2009 are analysed in terms of the incidence of Ippon, based on gender, age, weight category and the importance of competition.Results: Ippon appears, on average, at 55.52% of the meetings of males and 51.95% of the meetings of the females. Independent Samples T-test shows that these averages are significantly different at p = 0.033.In men's competitions Ippon represents an increasing share to the extent that increases the weightcategory: 52.34% in light categories, 57.15% in medium categories, 59.98% in heavy categories. One Way Anova shows that these differences are significant at p = 0.002. The lowest frequency of Ippon occurs in light female categories: 48.90%. The Independent Samples T-test shows that between this value and the frequency of53.91% corresponding to the occurrence of Ippon in the middle categories, there are also statistically significantdifferences at p = 0.025.Conclusions: in Judo competitions Ippon occurs following a normal statistical law, yet, some variables such as sex and the weight category can significantly influence the frequency of its occurrence. The age and the importance of the competition do not significantly influence the frequency of Ippon in the competition.